Serum ferritin concentration and iron stores in normal subjects - Walters, G. O. (1973)
The relationship between serum ferritin concentration and the amount of storage iron has been studied in normal subjects. A high degree of correlation was demonstrated between serum ferritin concentration and storage iron measured by quantitative phlebotomy. The possible advantages of assessing iron stores by using the serum ferritin concentration are discussed.